2007
DOI: 10.1038/nature05933
|View full text |Cite
|
Sign up to set email alerts
|

A transforming mutation in the pleckstrin homology domain of AKT1 in cancer

Abstract: Although AKT1 (v-akt murine thymoma viral oncogene homologue 1) kinase is a central member of possibly the most frequently activated proliferation and survival pathway in cancer, mutation of AKT1 has not been widely reported. Here we report the identification of a somatic mutation in human breast, colorectal and ovarian cancers that results in a glutamic acid to lysine substitution at amino acid 17 (E17K) in the lipid-binding pocket of AKT1. Lys 17 alters the electrostatic interactions of the pocket and forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

45
1,036
5
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,120 publications
(1,125 citation statements)
references
References 33 publications
45
1,036
5
18
Order By: Relevance
“…However, the SSCP from the tumours did not reveal any aberrantly migrating band compared with the wild-type bands from the normal tissues (data not shown). We repeated the experiments twice, including tissue microdissection, PCR, SSCP and DNA sequencing analysis to ensure the specificity of the results and found that the data were consistent.Because the previous study showed modest incidences of AKT1 E17K mutation (up to 8.2%) in a wide range of the cancers (Carpten et al, 2007), we expected to detect comparable AKT1 E17K mutations in our cancer specimens. However, we detected the AKT1 E17K mutation in the breast cancers (4.3%), but not in other cancers.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…However, the SSCP from the tumours did not reveal any aberrantly migrating band compared with the wild-type bands from the normal tissues (data not shown). We repeated the experiments twice, including tissue microdissection, PCR, SSCP and DNA sequencing analysis to ensure the specificity of the results and found that the data were consistent.Because the previous study showed modest incidences of AKT1 E17K mutation (up to 8.2%) in a wide range of the cancers (Carpten et al, 2007), we expected to detect comparable AKT1 E17K mutations in our cancer specimens. However, we detected the AKT1 E17K mutation in the breast cancers (4.3%), but not in other cancers.…”
mentioning
confidence: 80%
“…The AKT1 mutation was a missense mutation that substituted an amino acid (E17K) in the PH domain of AKT1. The AKT1 E17K mutation was found in 5 out of 61 (8.2%) breast cancers, 3 out of 51 (5.9%) colorectal cancers and 1 out of 50 (2.0%) ovarian cancers (Carpten et al, 2007). The E17K mutation was mutually exclusive with respect to PIK3CA mutation and loss of PTEN expression (Carpten et al, 2007).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Properly regulated activation of Akt depends on the integrity of the pleckstrin homology (PH) domain, which mediates its membrane translocation and subsequent phosphorylation at two regulatory sites, Thr308 in the kinase activation loop, and Ser473 in the C-terminal domain of the Akt family, only AKT2 mRNA is frequently overexpressed in human cancers [17]. Activation of Akt can also result from a dominant mutation that was identified in human tumours [3] and a point mutation of AKT2 has been reported in familial diabetes [9]. Ectopic expression of constitutively active Akt and even wild-type Akt2 results in oncogenic transformation in vitro and in vivo [4].…”
mentioning
confidence: 99%